Implementasi Sistem Informasi Akuntansi Terintegrasi untuk Meningkatkan Efisiensi Pelaporan Keuangan - Astri Ayu Pramesti; Nia Anisyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Implementation of an integrated accounting information system has become a key strategy for organizations in optimizing financial reporting efficiency. Management support factors play a central role in determining the success of this project. Commitment, resource allocation, active participation, and leadership in change management are important elements that define the level of management support. Management support is not only key to motivation, but also ensures that implementation can overcome obstacles and produce positive change in the organization. The success of implementation is not only measured from a technical perspective, but also from the added value presented by an integrated accounting information system for the efficiency of financial reporting. This research highlights the important role of management in designing, supervising and integrating accounting information systems. A deep understanding of business needs and financial reporting processes provides the basis for designing appropriate solutions. Implementation steps must be tailored to the unique characteristics of the organization, ensuring that the system adopted can accommodate specific needs and produce optimal results. Through this approach, organizations can improve the accuracy and speed of financial reporting, respond more effectively to market changes, and increase transparency.